The Brunswik Lens Model: a theoretical framework for advancing understanding of deceptive communication in autism - Blackhurst, Tiegan; Warmelink, Lara; Roestorf, Amanda; Hartley, Calum (Frontiers in Psychology, 2024)
Due to differences in social communication and cognitive functioning, autistic adults may have greater difficulty engaging in and detecting deception compared to neurotypical adults. Consequently, autistic adults may experience strained social relationships or face increased risk of victimization. It is therefore crucial that research investigates the psychological mechanisms that are responsible for autistic adults’ difficulties in the deception process in order to inform interventions required to reduce risk. However, weaknesses of extant research exploring deception in autism include a heavy focus on children and limited theoretical exploration of underlying psychological mechanisms. To address these weaknesses, this review aims to introduce a system-level theoretical framework to the study of deception in autistic adulthood: The Brunswik Lens Model of Deception. Here, we provide a comprehensive account of how autism may influence all processes involved in deception, including: Choosing to Lie (1), Producing Deception Cues (2), Perceiving Deception Cues (3), and Making the Veracity Decision (4). This review also offers evidence-based, theoretical predictions and testable hypotheses concerning how autistic and neurotypical adults’ behavior may differ at each stage in the deception process. The call to organize future research in relation to a joint theoretical perspective will encourage the field to make substantive, theoretically motivated progress toward the development of a comprehensive model of deception in autistic adulthood. Moreover, the utilization of the Brunswik Lens Model of Deception in future autism research may assist in the development of interventions to help protect autistic adults against manipulation and victimization.